Personalized bleeding management in total knee arthroplasty using reference change value: comparative analysis of tourniquet versus non-tourniquet techniques - Ugur, Fatih; Bildirici, Mehmet Akif; Taskin, Recep; Akar, Bedrettin; Albayrak, Mehmet; Karadeniz, Engin (Springer Science and Business Media LLC, 2025)
Abstract Introduction Total knee arthroplasty (TKA) is a commonly performed surgical procedure for the treatment of advanced-stage knee osteoarthritis. This study aims to compare perioperative blood loss between tourniquet-assisted and tourniquet-free TKA using the reference change value (RCV), a personalized analytical tool that accounts for both biological and analytical variability. Materials and methods A retrospective analysis was conducted on 137 patients (tourniquet group (n = 68) and non-tourniquet group (n = 69) who underwent primary TKA. Hematological parameters—including red blood cell count (RBC), hemoglobin (HGB), and hematocrit (HCT)—were evaluated preoperatively, on the day of surgery, and on postoperative day one. Blood loss was assessed using both conventional statistical methods and RCV-based analysis. Results No statistically significant differences were observed between the two groups in terms of age and gender (p > 0.05). Although preoperative hemoglobin levels were significantly different between groups (p < 0.05), there were no significant intergroup differences in pre- or postoperative RBC and HCT values. Traditional statistical analysis showed no significant difference in blood loss (p > 0.05). However, RCV analysis revealed that while bleeding had stabilized by the first postoperative day in the non-tourniquet group, it remained significantly elevated in the tourniquet group. Conclusions The findings suggest that RCV offers a more individualized and sensitive approach to assessing perioperative blood loss in TKA. Although conventional methods did not demonstrate significant differences, RCV analysis indicated a more rapid hemostatic response in the non-tourniquet group. Incorporating RCV into routine clinical practice may enhance patient-specific blood management and support earlier postoperative decision making.
Keywords: Research